2019
DOI: 10.1002/ejoc.201901146
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Photoredox/Transition‐Metal Catalysis for Carbon–Carbon Bond Formation Reactions

Abstract: Carbon–carbon bond formation reactions are of longstanding interest in organic chemistry. Improvements of the methods targeting its creation are still being performed, especially thanks to the development of innovative methodologies in transition metal catalysis and photocatalysis. This review will tackle the combination of transition metal and photoredox cycles to create carbon–carbon bonds, focusing on the four transition metals most reported in the literature in this domain: Ni, Pd, Au and Cu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 194 publications
1
31
0
Order By: Relevance
“…Based on literature data and previous experiments we may propose the following mechanism (Scheme ). As shown before, the base is crucial in this mechanism and plays an important role since the beginning with the deprotonation of the starting material A to give the anion B.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on literature data and previous experiments we may propose the following mechanism (Scheme ). As shown before, the base is crucial in this mechanism and plays an important role since the beginning with the deprotonation of the starting material A to give the anion B.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, the recent regain of interest in the literature for visible‐light catalysis, although described a century ago, appeared as an alternative strategy to build bonds and particularly the C−N bond . Indeed, several reactivity pathways are possible: reductive or oxidative quenching mechanism but also the Proton Coupled Electron Transfer strategy (PCET) .…”
Section: Introductionmentioning
confidence: 99%
“…The previous section included some examples of transition metals acting as Lewis acids, whereas this section focuses more on reactivity that is unique to transition metals, including inner sphere electron transfer events within the putative mechanisms. Transition metal complexes with achiral ligands have been widely used in combination with photocatalysts in racemic dual catalytic reactions [139,140], with nickel/photoredox catalysis becoming a commonly used combination [141,142]. Transition metal complexes with chiral ligands have also been used extensively in enantioselective catalysis.…”
Section: Transition Metal Catalysismentioning
confidence: 99%
“…A promising alternative approach is the use of aryl diazonium salts [14] under light activation, [15] which obviates the need for an additional oxidant, as the ArN 2 + serves as both, the oxidant and coupling partner. [16][17][18] Hashmi et al recently showed that this strategy enables the selective arylation of aryl silanes (C À SiMe 3 ) in the presence of C À BPin or CÀB(MIDA) as well as CÀhalogens, albeit under the limitation that the aryl diazonium salt had to be electronpoor. [19] In light of our recent studies that identified organogermanes as highly reactive functionality in gold-catalyzed couplings with ArH, [12g] we envisioned that we might be able to widen the scope in ArN 2 + electronics as well as add another dimension of modularity in biaryl construction by developing a selective arylation of CÀGeEt 3 under light activation that tolerates all other widely used and typical coupling functionalities, that is, C À BPin, C À SiMe 3 as well as halogens (C À I, C À Br and C À Cl).…”
mentioning
confidence: 99%
“…We subsequently explored the scope of the couplings and investigated especially those aryl germanes that would, as the corresponding aryl boronic acids, be unstable and sluggishly reactive or incompatible in the widely employed Pd-catalyzed Suzuki cross coupling, [21] that is, highly fluorinated, heterocyclic, sterically hindered as well as halogenated aryl germanes. [7] The presence of fluorine in ortho-or para-positions of the germane (1-3, see Table 1) as well as electron-rich heterocycles, such as the sterically demanding isoxazole (16), 2-and 3-substituted thiophenes (15,17), and a 1,3-benzodioxole (18) were well tolerated. Notably, analogous couplings of the latter previously needed metal and base additives to proceed.…”
mentioning
confidence: 99%